Pain from a Bullet Lingers on: An Uncommon Case of Lead Toxicity - Abraham, Albin (S. Karger AG, 2012)
Lead toxicity from a retained bullet as a cause for abdominal pain is rarely considered. Given its unpredictable latent period and nonspecific clinical symptoms, such cases are difficult to diagnose but may be fatal if unrecognized. We present the case of a 48-year-old man who presented with complaints of abdominal pain, weight loss and constipation. His past history was significant for a gunshot wound to the left hip about 20 years before. Radiographic studies confirmed the same with the presence of numerous intra-articular bullet fragments and a calcified hemarthrosis surrounding the left femoral head. Blood lead levels were elevated following which the patient was started on chelation therapy with succimer which resulted in symptomatic improvement. The aim of this paper is to highlight the importance of considering lead toxicity from a retained bullet as a cause of abdominal pain and to review the relevant literature.